2012
DOI: 10.1111/j.1537-2995.2012.03841.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo quality of leukoreduced apheresis platelets stored in a new platelet additive solution

Abstract: APs stored in PAS with 35% plasma carryover maintained pH over 5 days of storage and met current FDA criteria for radiolabeled recovery and survival. The use of PAS for storage of single-donor PLTs in clinical practice represents an acceptable transfusion product that reduces the volume of plasma associated with PLT transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
(26 reference statements)
2
31
1
Order By: Relevance
“…The studies were done sequentially and not randomized, the apheresis collections were done outside manufacturers' guidelines, and Plasmalyte was used for elutriation of platelets on the Haemonetics system, and it is also not a licensed storage solution. 6 Our data are the best results yet reported in the literature for extended stored platelets and demonstrate that platelet viability is better maintained in vitro than in vivo. Specifically, fresh radiolabeled autologous platelet survivals in the 38 normal subjects in our studies averaged 8.2 6 0.2 days, whereas platelets could be stored in vitro for 13 days with a residual in vivo lifespan of 4.6 6 0.3 for a combined in vitro/in vivo lifespan of almost 18 days, which is fully For personal use only.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The studies were done sequentially and not randomized, the apheresis collections were done outside manufacturers' guidelines, and Plasmalyte was used for elutriation of platelets on the Haemonetics system, and it is also not a licensed storage solution. 6 Our data are the best results yet reported in the literature for extended stored platelets and demonstrate that platelet viability is better maintained in vitro than in vivo. Specifically, fresh radiolabeled autologous platelet survivals in the 38 normal subjects in our studies averaged 8.2 6 0.2 days, whereas platelets could be stored in vitro for 13 days with a residual in vivo lifespan of 4.6 6 0.3 for a combined in vitro/in vivo lifespan of almost 18 days, which is fully For personal use only.…”
Section: Discussionsupporting
confidence: 70%
“…18 Murphy 19 suggested that each subject serve as his/her own control by comparing their fresh platelet recoveries and survivals to their poststorage data, and the FDA has adopted this strategy for assessing poststorage platelet quality. 6 We have previously evaluated plasma-stored Haemonetics or Spectra collected platelets for 5 to 8 days, and platelet recoveries and survivals were not significantly different between the 2 systems. 20 With the plasma studies as background, we determined how long platelets could be stored in a PAS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A variety of PASs have been developed. Standardized nomenclature labels PAS as PAS‐A to PAS‐G . All these solutions contain varying combinations of citrate, phosphate, acetate, magnesium, potassium, gluconate, and glucose, and the ingredients synergistically act to provide anticoagulation, membrane stabilization, metabolic substrates, buffering activity, apoptosis inhibition, and activation inhibition .…”
Section: Cold Pltsmentioning
confidence: 99%